2017
DOI: 10.17557/tjfc.356210
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECTS OF HIGH TEMPERATURE AT THE GROWING PERIOD ON YIELD AND YIELD COMPONENTS OF SOYBEAN [Glycine max (L.) Merr] VARIETIES

Abstract: This study was conducted at the Experimental Area of Cukurova University in 2015 and 2016 as a double crop growing season. The objective of this study was to determine the effect of high temperature on seed yield and some yield component of soybean [Glycine max (L.) Merr] varieties in double crop growing season in Mediterranean region in Turkey. The experimental design was a Randomized Complete Block with three replications. The Arısoy,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
22
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 31 publications
5
22
1
Order By: Relevance
“…During the pod formation (PF) to full seed development (FSD) rainfall, minimum temperature and humidity (RH-I and RH-II) showed significant positive association with seed yield whereas maximum temperature showed significant negative correlation with seed yield. This corroborates the findings of Onat et al, (2017). Onat et al, (2017) observed that the high temperature (Max T) negatively affected the seed yield of different soybean varieties.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…During the pod formation (PF) to full seed development (FSD) rainfall, minimum temperature and humidity (RH-I and RH-II) showed significant positive association with seed yield whereas maximum temperature showed significant negative correlation with seed yield. This corroborates the findings of Onat et al, (2017). Onat et al, (2017) observed that the high temperature (Max T) negatively affected the seed yield of different soybean varieties.…”
Section: Resultssupporting
confidence: 91%
“…This corroborates the findings of Onat et al, (2017). Onat et al, (2017) observed that the high temperature (Max T) negatively affected the seed yield of different soybean varieties. Mishra and Cherkauer (2010) also indicated that soybean crop yield is strongly correlated with maximum daily temperature during seed filling stage.…”
Section: Resultssupporting
confidence: 91%
“…The 2-year average 100-seed weight ranged between 14.2 -20.8g ( Table 5). The 100-seed weight and pod number per plant traits are the most important seed yield components in soybean (Onat et al, 2017). The highest 100-seed weight was obtained from KA-07-03-5 (20.8 g) and KA-07-03-9 lines (20.1 g).…”
Section: Sourcementioning
confidence: 99%
“…Tai and Hammons (1978) and Wynne and Isleib (1978) reported that the evaluation of peanut cultivars for genotype x environment interaction on yield and yield components seems to indicate only minor effects of genotype x location and genotype x year interactions, but there were relatively large genotype and genotype x location x year interactions. Arioglu and Ersoy (1987) and Onat et al (2017) findings showed that the average yield reduction was 19.9% and 29.5%, respectively in soybean varieties due to high temperature and the response against to high temperature of the soybean varieties were different.…”
Section: Introductionmentioning
confidence: 96%